Housing module with recyclable material in Huánuco - Jaimes Reátegui, Sumaya (2018)
The building of a housing module with recyclable materials contributes with an innovative construction system and allows changing environmental behavior. The objective research is the building of a housing module with recyclable material in Huánuco, transforming solid waste into useful elements for the building of houses, as well as presenting a proposal for a solution to the problem of housing deficit and problem of environmental pollution. The proposed methodology research generates new knowledge in the project experience of a project made or one to be built. Compression tests were carried out on the plastic bottles and the foundation was analyzed. It was concluded that the ring tires 16 are suitable for using in foundations and windows; the tires of tricycles are apt for the stem wall; the bottles (pet) of mineral water, filled with compact earth are suitable for the walls and the strips of tires are suitable for coverage.